Simulation of total concentration for ellipsoidal shape drops by using foward difference explicit method - Nur Syarafina Mohamed, 1988-; Jamalludin Talib, supervisor; Fakulti Sains (2012)
Thesis (Sarjana Sains (Matematik)) - Universiti Teknologi Malaysia, 2012